Nonlinear interaction of the elliptically polarized light with CdSxSe₁₋x quantum dots - Kulish, M.R.; Malysh, M.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
Peculiarities of the influence of ruby laser elliptically polarized light on the
absorption saturation in glass with CdSxSe₁₋x nanocrystals and absorption saturation on
light polarization were investigated. It was established that the change of ellipticity from
zero to unity does not influence the dependence of transmission on the light intensity.
Within the range of linear optics ( I₀<I*₁, where I₀ is the intensity of pumping,I₁ –
bleaching threshold) or within the range of absorption saturation ( I₀>I*₂, where I*₂ is
the absorption saturation threshold), light polarization at the entrance to glass with
CdSxSe₁₋x nanocrystals is congruent to light polarization at the exit from glass. Within the
range of a nonlinear dependence of absorption on the light intensity (I*₁< I₀<I*₂ ) ,
deformation of polarization ellipse increases, when nanocrystals for which C ⊥ E are
bleached, but for nanocrystals where E || C are not bleached this deformation has a
maximum value.